Evolução da demanda por assistência estudantil na UFSCar em função da implementação das ações afirmativas nos anos de 2007 a 2013 - Pinheiro, Tatiana Bianchini (2015)
This paper considers the evolution of the student´s needs for assistance in the Federal University of Sao Carlos (UFSCar), in Brazil, after the implementation of the Affirmative Actions by the year 2013. It is considered the year 2007 as previous reference implementation of Affirmative Action, which took place in 2008. The research topic was chosen on the grounds that their results relating to a partial analysis of the implementation of a public policy process, can contribute to improving the effectiveness of this policy. The overall objective of this research was to analyze whether there were changes in the demand for student assistance, and sought to also check whether, after the implementation of affirmative action, changes were needed in the work routines of ProACE (Sector of community and student affairs of the UFSCar) and in their departments directly involved with the student assistance. The research also presents the partial survey about the year of implementation of Affirmative Action in Brazilian federal universities, and to this end, consultations were held on the websites of these federal universities. The focus in this case was to understand the context in which the UFSCar was inserted when it decided to set affirmative action policies for admission of students. The method used is an exploratory research, based on documentary and field research. The conclusion of the study is that there was a great evolution in demand for student assistance in the analyzed period, as growth of 157% in the number of fellows, the tenfold increase spending on assistance grants and increasing by 84% the number places in student housing in addition to the creation, in 2011, of a home assistance fellow, but that can not be attributed only to the implementation of Affirmative Action, because until 2012 the UFSCar was involved in the process of expanding of REUNI (a government policy of expansion of places in Brazilian universities). Despite of the PROACE departments having to serve more students than they used to do, it was not observed significant changes in the routine to serve wider public benefited by student assistance.